2021
DOI: 10.1371/journal.pone.0259584
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance, virulence genes and biofilm formation in Enterococcus species isolated from milk of sheep and goat with subclinical mastitis

Abstract: This study is designed to discuss the antimicrobial resistance, virulence determinants and biofilm formation capacity of Enterococcus spp. isolated from milk of sheep and goat with subclinical mastitis in Qena, Egypt. The obtained isolates were identified by the VITEK2 system and 16S rDNA sequencing as E. faecalis, E. faecium, E. casseliflavus and E. hirae. Overall, E. faecalis and E. faecium were the dominant species recovered from mastitic milk samples. The antimicrobial susceptibility test evidenced multidr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 87 publications
(140 reference statements)
4
19
1
Order By: Relevance
“…Biofilm formation plays a considerable role in enterococcal infections and antibiotic resistance [75,76]. In this study, biofilm formation was observed in 81.1% of the isolates, which is concordant with [75,76]. A positive pairwise correlation was observed between biofilm production and both the MAR index and MDR.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Biofilm formation plays a considerable role in enterococcal infections and antibiotic resistance [75,76]. In this study, biofilm formation was observed in 81.1% of the isolates, which is concordant with [75,76]. A positive pairwise correlation was observed between biofilm production and both the MAR index and MDR.…”
Section: Discussionsupporting
confidence: 66%
“…Biofilm formation plays a considerable role in enterococcal infections and antibiotic resistance [75,76]. In this study, biofilm formation was observed in 81.1% of the isolates, which is concordant with [75,76].…”
Section: Discussionsupporting
confidence: 64%
“…Enterococci also still play an important role in the production of fermented dairy products, such as some cheeses, in extension of the shelf life and improvement of their taste, texture, and aroma [ 4 ]. According to data provided by various authors, enterococci may occur naturally or as contaminants of milk and dairy products [ 5 , 6 , 7 , 8 , 9 , 10 ]. Enterococci isolated from cheese make up one-third of all LAB from this matrix, while they constitute up to 20% of all bacteria isolated from milk [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…They also show lower susceptibility, to aminoglycosides, lincosamides and quinolones. Resistance to ampicillin, tetracyclines, macrolides, aminoglycosides at high level, chloramphenicol, trimethoprim/sulfamethozaxole, quinolones and streptogramins is not intrinsic but acquired, as is resistance to glycopeptides [ 5 , 9 , 11 , 13 ]. Improper, uncontrolled use of antibiotics has led to an increase in the number of resistant strains, including multidrug-resistant strains among enterococci.…”
Section: Introductionmentioning
confidence: 99%
“…The first or latest cases of antibiotic resistance of chosen foodborne pathogens in different parts of the world. References [ 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 , 291 , 292 , 293 , 294 , 295 , 296 , 297 , 298 , 299 , 300 , 301 , 302 ] are cited in the Supplementary Materials.…”
mentioning
confidence: 99%